How can logistics service providers foster supply chain collaboration in logistics triads? insights from the Italian grocery industry - Prataviera, Lorenzo Bruno; Creazza, Alessandro; Dallari, Fabrizio; Melacini, Marco (Emerald, 2021)
Purpose: Collaborative solutions are increasingly being proposed to generate value in supply chains. Concurrently, firms have progressively outsourced logistics operations to logistics service providers (LSPs). However, many questions remain unsolved regarding the role played by LSPs in supporting supply chain collaboration (SCC) in triadic rather than dyadic contexts. This study aims to explore the relational mechanisms that LSPs can leverage to foster value creation through collaboration, elaborating on an existing theory about SCC by focussing on logistics triads. Design/methodology/approach: By leveraging the view of the network theory, a multiple case study approach was adopted. Seven cases having logistics triads as units of analysis were identified and analysed within the Italian grocery supply chain, allowing for empirical investigation with a middle-range approach to extend the previous theory. Findings: LSPs are pivotal actors that can actively promote SCC. LSPs can exploit large volumes and asset availability to increase efficiency while improving logistics flexibility and developing regular and trustworthy relationships with the other triad members. Building upon their logistics capabilities and the relational mechanisms in place, LSPs can help manufacturers collaborate with retailers by improving mutual trust and communication, acting as trust builders or trust conductors within the triad. Originality/value: The study explores the role of LSPs in logistics triads, extending the previous literature. It highlights that LSPs facilitate not only supply and demand integration but also relational integration between firms. Trust emerges as a fundamental building block for SCC, as LSPs can look beyond economic benefits to foster partnerships that empower the co-development of original collaborative solutions.
Keywords: Collaboration; Fast moving consumer goods; Logistic Service Industry; Logistics management; Case Studies; Supply-chain management